A streamlined synthetic approach to the truncated linear trisaccharide fragment of QS-21 - Lin, Jhe-Sian; Tzeng, Zheng-Hao; Dumalaog, Jasper S.; Hung, Shang-Cheng (Frontiers in Chemistry, 2025)
QS-21, a potent immunostimulatory saponin obtained from Quillaja saponaria Molina, a soapbark tree native to Chile, has undergone extensive study for its broad application as a vaccine adjuvant against various infectious diseases and cancers. The structure of QS-21, which features a linear oligosaccharide moiety, provides a critical attachment site for both the labile acyl side chain and the distinctive sugar unit that defines each major saponin variant. In this study, we present an efficient synthetic approach to the truncated linear trisaccharide fragment of QS-21, circumventing the challenges associated with the synthesis of the rare sugar D-fucose. The synthesis of this linear trisaccharide enables streamlined access to a homogeneous QS-21.